The role of evidence in consumer choice of non‐prescription medicines. (29th May 2019) - Bevan, Marc; Ng, Yee Ching; Cooper, Joyce; Robertson, Jane; Walkom, Emily; Chiu, Simon; Newby, David A.
Abstract: Objectives: To identify factors influencing Australian consumer decision‐making and attitudes towards non‐prescription medicine (NPM) purchases, pharmacy's role in providing these medications and views around sources of evidence for effectiveness of these products. Methods: Cross‐sectional survey of a general population sample of 1731 adults using an Australian online consumer panel stratified by gender, age and location (State/Territory). Beliefs about NPM purchases and evidence of their efficacy were assessed using a 5‐point Likert scale (strongly disagree‐strongly agree). Non‐parametric measures (Ridit analysis and Mann–Whitney U ‐test) were used to explore associations between responses and previous experience with medicines. Key findings: The most important factors when purchasing NPMs were effectiveness and safety. However, personal experience was the most common method of determining effectiveness. Most respondents believed buying NPMs in pharmacies gave access to advice, but were less likely to agree that pharmacies were associated with safe and effective treatments. Around half the respondents agreed that it is wrong to sell treatments lacking scientific evidence; many also agreed that it is up to consumers to decide what they want even without scientific evidence. Individuals experiencing an ineffective NPM were less likely to trust scientific evidence of efficacy as the sole source of effectiveness information; regular prescription medicine users often agreed that scientific evidence is needed to support effectiveness. Conclusions: Consumers have conflicting views regarding the need for scientific evidence and the desire for patient autonomy in NPM purchases. This presents a challenge for pharmacists wishing to maintain professional obligations to provide evidence‐based treatments to consumers.